2018
DOI: 10.1007/s00253-017-8734-2
|View full text |Cite
|
Sign up to set email alerts
|

Role and mechanism of cell-surface hydrophobicity in the adaptation of Sphingobium hydrophobicum to electronic-waste contaminated sediment

Abstract: Sphingomonads are isolated at exceptionally high frequency from organic polluted environments and assumed to be more hydrophobic than other Gram-negative bacteria. However, the potential roles of cell-surface hydrophobicity (CSH) in the cell survival in polluted environment, as well as the mechanisms underlying the CSH of sphingomonads, remain unclear. Sphingobium hydrophobicum C1 is a highly hydrophobic sphingomonad isolated from electronic-waste contaminated sediment. In this study, we found that exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Sphingobium hydrophobicum C1 T (= CCTCC AB 2015198 = KCTC 42740) was isolated from e-waste contaminated sediment in Guiyu, China (Chen et al, 2016). Strain C2, a hydrophilic variant of strain C1 T , was obtained by cell passage for ∼100 generations in LB medium (Chen et al, 2017). Strains C3 and C4 were isolated from the first-round subculture (within 10 generations) of strains C1 T and C2 in LB medium, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sphingobium hydrophobicum C1 T (= CCTCC AB 2015198 = KCTC 42740) was isolated from e-waste contaminated sediment in Guiyu, China (Chen et al, 2016). Strain C2, a hydrophilic variant of strain C1 T , was obtained by cell passage for ∼100 generations in LB medium (Chen et al, 2017). Strains C3 and C4 were isolated from the first-round subculture (within 10 generations) of strains C1 T and C2 in LB medium, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The CSH of cells in the late-exponential growth phase was measured using the microbial adhesion to hydrocarbon (MATH) protocol as described previously (Chen et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When other carbon sources were present, phenol addition mostly caused an increase in CSH, regardless of the cells' surface being primarily hydrophobic or hydrophilic, but the observed changes were smaller for P. plecoglossicida IsA. Chen et al [47] have demonstrated that Sphingobium hydrophobicum C1 cells with high cell surface hydrophobicity exposed to deca-bromophenyl ether remained hydrophobic, while the hydrophilic Sphingobium hydrophobicum C2 remained hydrophilic.…”
Section: Cell Membrane Permeability and Surface Hydrophobicitymentioning
confidence: 99%
“…It exhibits great resistance to multiple heavy metals and can degrade common organic pollutants, such as phthalate esters, diphenyl ether, biphenyl, and chlorobenzene ( 3 ). Compared with its hydrophilic variant C2 obtained by continuous subculture, it has a higher colonization ability and more adsorption capacity for hydrophobic pollutants ( 3 , 20 ). The upregulated expression of some outer membrane proteins in strain C1 detected by comparative proteome analysis may be a key hydrophobic factor ( 20 ).…”
Section: Introductionmentioning
confidence: 99%